Resiliência e uso de drogas: como a resiliência e seus aspectos se relacionam aos padrões no uso de drogas por adolescentes - Amato, Tatiana de Castro [UNIFESP] (2010)
The aim was assess how resilience and its factors are related to different drug use patterns in adolescents. Private school students from São Paulo (Brazil) were selected by a representative, stratified and cluster sample. It was applied a self-report questionnaire proposed by WHO measuring alcohol, binge drinking, tobacco and other drugs (marijuana, inhalants, tranquilizers, stimulants, cocaine, ecstasy and crack) 30-day use. The resilience was assessed by Resilience Scale, which in Brazilian validation the main factor was named “capacity to act based on ones values”. The economic class was measured by ABEP scale. Weighted data were analyzed by descriptive, bivariate (GLM), cluster analysis and logistic regression statistics. Significance level was set at 5%. The sample was comprised of 2691 students with mean age 16 (CI=15.9-16.1), 52% were female and 95.5% were from upper economic classes. The most prevalent drug consumption was alcohol (50.2%), followed by tobacco (14.1%) and other drugs (11.6%). Binge drinking was related by 31.8%.Cluster analysis identified four groups according to 30-day drug use: do not use drugs, alcohol, alcohol/ binge drinking/ tobacco, alcohol/ binge drinking/ tobacco/ other drugs. The resilience was not associated with different drug use patterns in this population. However, the factor “capacity to act based on ones values” that evaluate self-steam, determination, self-discipline, good mood, readiness to help and adaptability, contribute to decrease the odds of alcohol use, binge drinking and other drug use. The main protect factors for this drug use pattern was self-discipline and determination. Self-discipline also decreased the odds of alcohol associated with binge drinking and tobacco use. These results highlight the relevance of aspects related to “capacity to act based on ones values”, especially self-discipline and determination, to drug use prevention in adolescence.